Does Morality Require God? - Ahmad, Saiyad Fareed (Intellectual Discourse, 2003)
A series of arguments have been offered in favour of a God-based ethical and moral system by convincingly refuting parallel, competing systems like secularist, relativistic and situational ethics which advocate the alleged superiority of their standards devoid of God or religious concepts and precepts. Specifically, the article has examined (i) popular theories of Western ethics, (ii) religious ethics, particularly that of Islamic ethics and its sole dependence and reliance on God and religion, and (iii) an overview and an enunciation and articulation of Islamic perspective on morality. This perspective is provided in the context of modern ethical theories by comparing secular theories with Islamic ethics wherein morality is inextricably linked with religion.